Fecal Lcn-2 level is a sensitive biological indicator for gut dysbiosis and intestinal inflammation in multiple sclerosis - Yadav, Sudhir K.; Ito, Naoko; Mindur, John E.; Kumar, Hetal; Youssef, Mysra; Suresh, Shradha; Kulkarni, Ratuja; Rosario, Yaritza; Balashov, Konstantin E.; Dhib-Jalbut, Suhayl; Ito, Kouichi (Frontiers in Immunology, 2022)
Multiple Sclerosis (MS) has been reported to be associated with intestinal inflammation and gut dysbiosis. To elucidate the underlying biology of MS-linked gut inflammation, we investigated gut infiltration of immune cells during the development of spontaneous experimental autoimmune encephalomyelitis (EAE) in humanized transgenic (Tg) mice expressing HLA-DR2a and human T cell receptor (TCR) specific for myelin basic protein peptide (MBP87-99)/HLA-DR2a complexes. Strikingly, we noted the simultaneous development of EAE and colitis, suggesting a link between autoimmune diseases of the central nervous system (CNS) and intestinal inflammation. Examination of the colon in these mice revealed the infiltration of MBP-specific Th17 cells as well as recruitment of neutrophils. Furthermore, we observed that fecal Lipocalin-2 (Lcn-2), a biomarker of intestinal inflammation, was significantly elevated and predominantly produced by the gut-infiltrating neutrophils. We then extended our findings to MS patients and demonstrate that their fecal Lcn-2 levels are significantly elevated compared to healthy donors (HDs). The elevation of fecal Lcn-2 levels correlated with reduced bacterial diversity and increased levels of other intestinal inflammation markers including neutrophil elastase and calprotectin. Of interest, bacteria thought to be beneficial for inflammatory bowel disease (IBD) such as Anaerobutyricum, Blautia, and Roseburia, were reduced in fecal Lcn-2-high MS patients. We also observed a decreasing trend in serum acetate (a short-chain fatty acid) levels in MS Lcn-2-high patients compared to HDs. Furthermore, a decrease in the relative abundance of Blautia massiliensis was significantly associated with a reduction of acetate in the serum of MS patients. This study suggests that gut infiltration of Th17 cells and recruitment of neutrophils are associated with the development of gut dysbiosis and intestinal inflammation, and that fecal Lcn-2 level is a sensitive biological indicator for gut dysbiosis in multiple sclerosis.